2018
DOI: 10.1088/1361-6463/aaa650
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tuning on band gaps of 2D phononic crystals considering adhesive layers

Abstract: Phononic crystals are very attractive in many applications, such as noise reduction, filters and vibration isolation, due to their special forbidden band gap structures. In the present paper, the investigation of tunable band gaps of 2D phononic crystals with adhesive layers based on thermal changing is conducted. Based on the lumpedmass method, an analytical model of 2D phononic crystals with relatively thin adhesive layers is established, in which the inplane and outofplane modes are both in consideration. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 49 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…From these data, we found that when the temperature changed from 20 °C to 80 °C, the young's modulus of PBT could experience a change of three orders of magnitude. However, the PBT maintained an elastic solid state even at a significant reduction in Young's modulus during the varied temperature [27]. The Poisson ratio (0.3) and mass density (1180 kg/m 3 ) of PBT were independent of the temperature.…”
Section: Numerical Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…From these data, we found that when the temperature changed from 20 °C to 80 °C, the young's modulus of PBT could experience a change of three orders of magnitude. However, the PBT maintained an elastic solid state even at a significant reduction in Young's modulus during the varied temperature [27]. The Poisson ratio (0.3) and mass density (1180 kg/m 3 ) of PBT were independent of the temperature.…”
Section: Numerical Resultsmentioning
confidence: 95%
“…The introduction of polybutylene terephthalate (PBT) into periodic structures makes it possible to regulate the band structure [26,27]. As a smart composite material, PBT is a kind of composite material with a unique temperature dependence.…”
Section: Introductionmentioning
confidence: 99%
“…These properties of spin wave would be helping for designing specific magnetic crystal structures for controlling spin wave. The artificial crystal structures have been attracted tremendous research efforts; the well studied being optical photonic crystals and acoustic phononic crystals [138][139][140][141][142][143][144][145][146][147][148][149][150][151][152]. The third category of artificial magnetic crystal structures, so-called magnonic crystals, are the magnetic analog of photonic crystals and phononic crystals and are useful for manipulating of spin wave.…”
Section: Impurity Dependencementioning
confidence: 99%
“…This unique ability endows PCs with a bright prospect to be applied in the area of noise suppression [1], filter [2,3], shock insulation [4,5], acoustic transducers [6], and so on. For promoting engineering applications of forbidden band gaps, many effective active adjusting and manipulating methods based on altering mechanical properties, sizes of crystal lattice, and topological structures have attracted a great deal of attention [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%